Morphometric Analysis of Infraorbital Foramen in the Telangana Population - Masooma Begum; B H Shiny Vinila (Academia Anatomica International, 2019)
Introduction: The infraorbital foramen gives passage to the infraorbital nerve and vessels. The infraorbital nerve needs to be blocked to anaesthetise lower eyelid, lateral nose, upper lip, upper teeth and gingivae for various dental treatments or maxillofacial surgical procedures. The present study was undertaken to determine the size and location of the infraorbital foramen in Telanagana population. Subjects and Methods: The study was conducted on 52 skulls. The size was determined by taking maximum vertical and maximum transverse diameters. The location of the infraorbital foramen was determined by measuring the distance between the centre of the foramen and infraorbital margin, the distance from the centre of the foramen to piriform aperture, and the distance from the centre of the foramen to anterior nasal spine. Results: The mean vertical and transverse diameter of the infraorbital foramen was 3.57 mm and 2.88 mm on the right side and 3.18 mm and 2.98 mm on the left side respectively. The mean distance from the centre of the infraorbital foramen to infraorbital margin, anterior nasal spine and piriform aperture was 7.31mm, 32.46 mm and 16.57 mm on the right side and 7.27 mm, 31.70 mm and 16.13 mm on the left side respectively.  Conclusion: Knowledge about the exact size and location of the infraorbital foramen will be useful for the dental and maxillofacial surgeons to blocking the infraorbital nerve and also while performing various therapeutic procedures in this region.